2002
DOI: 10.1002/1522-2675(200207)85:7<2073::aid-hlca2073>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an Enantiomerically Pure 1,3-Thiazole-5(4H)-thione and Its Stereoselective 1,3-Dipolar Cycloaddition with an Azomethine Ylide

Abstract: Starting from the enantiomerically pure 2H-azirin-3-amines (R,S)-4 and (S,S)-4, the enantiomeric, optically active 4-benzyl-4-methyl-2-phenyl-1,3-thiazole-5(4H)-thiones (R)-1 and (S)-1, respectively, have been prepared (Schemes 2 and 3). In each case, the reaction of 1 with N-(benzylidene)[(trimethylsilyl)methyl]amine (2) in HMPA in the presence of CsF and trimethylsilyl triflate gave a mixture of four optically active spirocyclic cycloadducts (Scheme 4). Separation by preparative HPLC yielded two pure diaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…67a ). It is worth noting that N -alkyl azomethine ylides (section ) tend to react with ketone and aldehyde carbonyls via 1,3-dipolar cycloaddition instead of the direct nucleophilic attack observed for semistabilized 2 -azaallyl anions. Hydrolysis of the imine functionality in the products 67 was readily achieved in high yield by treatment with aqueous HCl.…”
Section: -Azaallyl Anionsmentioning
confidence: 99%
“…67a ). It is worth noting that N -alkyl azomethine ylides (section ) tend to react with ketone and aldehyde carbonyls via 1,3-dipolar cycloaddition instead of the direct nucleophilic attack observed for semistabilized 2 -azaallyl anions. Hydrolysis of the imine functionality in the products 67 was readily achieved in high yield by treatment with aqueous HCl.…”
Section: -Azaallyl Anionsmentioning
confidence: 99%
“…13 C-NMR: 167.9 (s, C (7) -3-dichloroacetyl-4,4-dimethyl-5-methylsulfanyl-1,3-thiazolidine (7a) and 2, 3,6, [1,3] 4.73,Cl 19.57,N 3.87,S 17.70;found: C 49.50,H 4.48,Cl 19.77,N 3.99,S 17.40.…”
Section: Scheme 10mentioning
confidence: 99%
“…-A convenient synthesis of 4,4-disubstituted 1,3-thiazole-5(4H)-thiones 1, the less well-known di-sulfur analogs of 1,3-oxazol-5(4H)-ones (azlactones), was developed in the eighties [2]. The method also allowed the preparation of enantiomerically pure examples [3]. In a large series of experiments, it has been shown that the C=S group of 1 is the most reactive part of the molecule [4].…”
mentioning
confidence: 99%
“…The synthesis of phosphorus ylides is an important reaction in organic chemistry because of the application of these compounds in the synthesis of organic products 1–29. Several methods have been developed for the preparation of phosphorus ylides 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…Michael addition of phosphorus(III) compounds such as triphenylphosphine to acetylenic esters leads to reactive 1,3‐dipolar intermediate betaines, which are not detected even at low temperatures 14. These unstable species can be trapped by a protic reagent, ZH, such as methanol, amide, or imide, to produce various compounds, for example, ylides 4–29.…”
Section: Introductionmentioning
confidence: 99%